THE IMPACT OF COVID – 19 PANDEMIC ON THE QUALITY OF WORK WITHIN A MANUFACTURING COMPANY BASED ON CONTINUOUS IMPROVEMENT - Mariana SEHLEANU; Elena-Simona FLORE (Annals of the University of Oradea: Economic Science)
The study was conducted in a manufacturing company with foreign subscribed capital, that has implemented several principles on continuous improvement, and aims to reveal the impact of COVID – 19 pandemic on the quality of work. In recent years, in order to streamline and improve the company`s activity, several measures related to the production processes have been implemented, which obviously also involved the quality of the work performed. Since the company adopted the principles of continuous improvement, the outcomes were obvious, both in terms of economic-financial indicators and in terms of the skills and competencies of the workforce. The role of the workforce in continuous improvement is a vital one, therefore the company has successfully implemented working procedures that had led to the standardization of the way of working. With the COVID–19 pandemic, there have been certain changes at the company level, with different impacts on employees and their work. Based on the company`s internal data, this paper analyzes the results of the evaluation of employees' work performance, over a period of four years (2019 - 2022).